Control system and monitoring credit operations as a tool of counteracting of the legalization of incomes, received by criminal way - Маркарян, Ганна Оганесівна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
We propose a tool of counteracting of the legalization of incomes, received by criminal way, based on the methodology of system analysis and communication with the functional features of the control system of crediting. The analysis of financial monitoring and of banking activities is carried out, the structure of a control system and of a monitoring of credit operations is offered, the criteria for decision-making are formulated, software is created.